More fans at any cost? Analysing the economic effects of the ratio of fans to non-fans in a customer portfolio considering electronic word of mouth. Issue 3 (2nd July 2016) - Banz, Marion; Grosswiele, Laura; Huber, Johannes; Probst, Florian
Abstract: Consumers in online social networks increasingly rely on electronic word of mouth (eWOM) when making purchase decisions. Recent research suggests positive effects of the resulting strong exposure of fans to eWOM on cash flows. Consequently, companies follow the popular belief that they should maximise their number of fans by intensively promoting their fan pages. However, even though the sentiment of eWOM on fan pages is prevailingly positive, sheer maximisation of fans in a customer portfolio must be critically reflected upon: while fans yield higher expected cash flows than non-fans, the associated risk in terms of these cash flows' volatility might also be considerably higher. Thus, diversifying risk by keeping a share of non-fans – or even increasing it – might be economically reasonable. By drawing on a portfolio selection theory-based model and real-world data, this paper analyses the ratio of fans to non-fans and its economic effects in customer portfolios.